2014
DOI: 10.9734/arrb/2014/10526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Emitting Diode High Intensity on Growth of Lettuce (Lactuca sativa L.) and Broccoli (Brassica oleracea L.) Seedlings

Abstract: Aims: To evaluate the effects of high intensity LED light with different wavelengths (red, blue, green and magenta filter) in physiology and absorption spectrum of lettuce (Lactuca sativa L.) and broccoli (Brassica oleracea L.) seedlings, with exposure times of 12 hours, in order to improve the growth of vegetables. Study Design: Four treatments of light (red, blue, green, magenta filter) and one control (white light). The experimental design was completely randomized, with two replications of 14 seedlings per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
2
0
2
Order By: Relevance
“…Available research is concentrated on the effects of LED irradiance during seedlings growth; both in closed environment chambers and in greenhouses (as supplemental lighting) [17,18]. Moreover, few works are focused on broccoli seedlings under LED light [19]. Most studies showed the beneficial effects of red light (670-700 nm) combined with blue light (425-490 nm) on seedling quality but the proper ratio of red to blue light seems to be species/cultivar specific and may vary depending on environment factors and cultivation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Available research is concentrated on the effects of LED irradiance during seedlings growth; both in closed environment chambers and in greenhouses (as supplemental lighting) [17,18]. Moreover, few works are focused on broccoli seedlings under LED light [19]. Most studies showed the beneficial effects of red light (670-700 nm) combined with blue light (425-490 nm) on seedling quality but the proper ratio of red to blue light seems to be species/cultivar specific and may vary depending on environment factors and cultivation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Очевидно, что значение имеет спектральный диапазон излучаемой световой энергии. Наибольшее значение имеют синий и красный спектры и их сочетание в облучательной установке [6][7][8][9][10].…”
Section: новые технологии и оборудованиеunclassified
“…Faktor lingkungan yang berpengaruh terhadap perkecambahan benih yaitu kelembaban, temperatur, oksigen, dan kadang-kadang bagi benih tertentu diperlukan pula cahaya (Kartasapoetra, 2003;Boyd dan Acker, 2004;Washa, 2015). Selain faktor lingkungan, cahaya dengan intensitas tinggi yang mampu meningkatkan pertumbuhan kecambah (Darko et al, 2014;Pardo et al, 2014;Ooi et al, 2016).…”
Section: Uji Daya Tumbuhunclassified